Toxicity of per- and polyfluoroalkyl substances to aquatic vertebrates - Ma, Tingting; Wu, Peng; Wang, Lisha; Li, Quanguo; Li, Xiuhua; Luo, Yongming (Frontiers in Environmental Science, 2023)
Rapid industrial development and extensive use of chemicals have resulted in elevated concentrations of emerging contaminants worldwide, posing a substantial threat to the ecological environment and human health. Per- and polyfluoroalkyl substances (PFASs) have been recognized as emerging pollutants that are widely distributed and accumulated in the environment and they have drawn the attention of scholars for several decades. The variety, long-term use, and long-distance transmission of PFASs have resulted in the ubiquitous contamination of global ecosystems, especially in aquatic environments. Ever since perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) were added to the Stockholm Convention on Persistent Organic Pollutants (POPs), they have become the most typical, eye-catching, and frequently investigated PFASs. Owing to the high stability and bioaccumulation of PFASs, as well as the adverse impact on the endocrine, immune, and nervous systems, investigating their contamination levels, risk of transfer along the food chain, and ecotoxicity should be prioritized. In addition to the important evolutionary significance as primitive vertebrates and the main consumers of aquatic environment, fishes generally exist in various aquatic food chains from the bottom to the top and occupy a critical position in terms of aquatic ecology protection; while amphibians, as the key link from aquatic to terrestrial organisms, are highly sensitive to different environmental pollutants. This review is a comprehensive summary of the toxic effects and toxicity-related factors of PFASs on aquatic vertebrates, mainly Pisces and Amphilla organisms, the characteristics of different aquatic vertebrates in toxicity investigations, and the evaluation of the feasibility of PFASs substitute applications.